A cationic polymethacrylate-copolymer acts as an agonist for β-amyloid and an antagonist for amylin fibrillation. Issue 14 (7th March 2019) - Sahoo, Bikash R.; Genjo, Takuya; Nakayama, Takahiro W.; Stoddard, Andrea K.; Ando, Toshio; Yasuhara, Kazuma; Fierke, Carol A.; Ramamoorthy, Ayyalusamy
Abstract : This study demonstrates the modulation of amyloid aggregation of two human proteins, amyloid-beta and amylin, by a cationic polymer (PMAQA). Abstract : In humans, β-amyloid and islet amyloid polypeptide (IAPP, also known as amylin) aggregations are linked to Alzheimer's disease and type-2 diabetes, respectively. There is significant interest in better understanding the aggregation process by using chemical tools. Here, we show the ability of a cationic polymethacrylate-copolymer (PMAQA) to quickly induce a β-hairpin structure and accelerate the formation of amorphous aggregates of β-amyloid-1-40, whereas it constrains the conformational plasticity of amylin for several days and slows down its aggregation at substoichiometric polymer concentrations. NMR experiments and microsecond scale atomistic molecular dynamics simulations reveal that PMAQA interacts with β-amyloid-1-40 residues spanning regions K16-V24 and A30-V40 followed by β-sheet induction. For amylin, it binds strongly close to the amyloid core domain (NFGAIL) and restrains its structural rearrangement. High-speed atomic force microscopy and transmission electron microscopy experiments show that PMAQA blocks the nucleation and fibrillation of amylin, whereas it induces the formation of amorphous aggregates of β-amyloid-1-40. Thus, the reported study provides a valuable approach to develop polymer-based amyloid inhibitors to suppress the formation of toxic intermediates of β-amyloid-1-40 and amylin.